Carry on : the rise and fall of Simon Snow - Rowell, Rainbow (New York : St. Martin's Griffin, 2015)
Simon Snow is the worst Chosen One who's ever been chosen. Half the time, Simon can't even make his wand work, and the other half, he starts something on fire. His mentor's avoiding him, his girlfriend broke up with him, and there's a magic-eating monster running around, wearing Simon's face. His roommate Baz would be having a field day with all this, if he were here -- it's their last year at the Watford School of Magicks, and Simon's infuriating nemesis didn't even bother to show up.
"A novel"--Cover.
Map on lining papers.
Keywords: Magic -- Juvenile fiction; Vampires -- Juvenile fiction; Magicians -- Juvenile fiction; Monsters -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Boarding schools -- Juvenile fiction; Schools -- Juvenile fiction; Fantasy fiction; Vampire fiction